Reaction Pathways and Mechanisms in Thermocatalytic Biomass Conversion I : Cellulose Structure, Depolymerization and Conversion by Heterogeneous Catalysts /: Cellulose Structure, Depolymerization and Conversion by Heterogeneous Catalysts. (2015) - Unknown
No abstract available